Automation vs. Human Touch: Ethical Implications of AI in HR Decision-Making. (Journal of Informatics Education and Research, 2025)
The growing adoption of Artificial Intelligence (AI) in Human Resource (HR) management has transformed traditional practices, particularly in areas like recruitment, performance evaluation, employee engagement, and workforce planning. While automation enhances efficiency, scalability, and objectivity in decision-making, it raises significant ethical concerns related to transparency, accountability, and the erosion of human judgment. This paper investigates the ethical implications of integrating AI into HR decision-making processes, focusing on the tension between automation and the human touch. By analyzing case studies, regulatory policies, and emerging HR technologies, the study examines potential risks such as algorithmic bias, data privacy violations, dehumanization of employee interactions, and the dilution of empathy and contextual understanding. The paper further explores ethical frameworks and principles that should guide AI deployment in HR, emphasizing the importance of explainable AI, informed consent, and inclusive design. It also advocates for hybrid models that blend algorithmic support with human oversight to maintain fairness, trust, and emotional intelligence in organizational decision-making. The findings underscore the need for HR professionals and developers to collaborate in creating AI systems that align with ethical standards and organizational values. As AI becomes more pervasive in HR, preserving the balance between technological efficiency and human empathy will be crucial for sustainable and ethical workforce management.